1973
DOI: 10.1901/jeab.1973.20-385
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Effectiveness of the Differential‐reinforcement‐of‐low‐rate Schedule

Abstract: Pigeons and rats wvere used in a yoked-control design that equated the reinforcement distributions of differential-reinforcemiient-of-lowv-rate and variable-interval schedules. Both a between-subjects design and a wvithin-subjects design found response rate higher for the variable-interval schedule than for the differential-reinforcemiient-of-lowv-rate schedule, thus delnionstrating the effcctiveness of the differential-reinforceiiient-of-low-rate contingency.The interresponse-time distributions were unimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

1973
1973
1994
1994

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
2
15
1
Order By: Relevance
“…Richardson (1973) investigated whether the interresponse-time distribution obtained when a 15-sec interresponse time was required would be maintained when the requirement was removed but the temporal distribution of food presentations was maintained by a variable-interval schedule. Under the variableinterval schedules, the modal interresponse times were less than with the differentiation procedure, and the shapes of the distributions changed from approximate symmetry toward positive skewness.…”
Section: Discussionmentioning
confidence: 99%
“…Richardson (1973) investigated whether the interresponse-time distribution obtained when a 15-sec interresponse time was required would be maintained when the requirement was removed but the temporal distribution of food presentations was maintained by a variable-interval schedule. Under the variableinterval schedules, the modal interresponse times were less than with the differentiation procedure, and the shapes of the distributions changed from approximate symmetry toward positive skewness.…”
Section: Discussionmentioning
confidence: 99%
“…One of Anger's (1956) original observations on the responding of normal rats on a DRL schedule was that the "low rates" are in part due to the fact that only a restricted class of responses that fulftll the DRL delay requirement are reinforced, while all others that do not satisfy the DRL contingency are not reinforced and subsequently become extinguished. In an unpublished study, Richardson (1972) has compared the DRL and VI performance of rats and pigeons under conditions of equal reinforcement density and interreinforcement times by using a yoked control procedure. He found that for all Ss, the level of responding was lower on DRL than on VI, thus supporting the conclusion that the DRL contingency (i.e., differential reinforcement of particular IRTs), quite apart from the reinforcement density, leads to response suppression.…”
Section: Discussionmentioning
confidence: 99%
“…That IRTs can be differentiated is argued by few. Since Anger's (1956) classic paper, however, numerous procedures have been developed to demonstrate conclusively that IRT differentiation can or cannot account for schedulecontrolled performance (see Ferster & Skinner, 1957;Galbicka & Platt, 1984McDowell & Wixted, 1986;Platt, 1979;Richardson, 1973 (1986, pp. 377-378).…”
Section: )mentioning
confidence: 99%